How Can We Predict Success in Poor Responders? - Alina Elena BORDEA; Elvira BRATILA; Diana MIHAI; Marina ANTONOVICI; Claudia MEHEDINTU; Andreea CARP-VELISCU (Modern Medicine)
Objectives: The aim of this study was to evaluate how can we predict success in poor responder patients in terms of pregnancy rate and live birth rate. Material and method: This study is a review of the newest papers that have in the center the poor responders undergoing treatment involving assisted reproductive techniques (ART). Outcomes: The results show that the most reliable factors when counseling a poor responder patient are age and Anti-Müllerian hormone (AMH) level. Conclusions: The most important factors that influence pregnancy rate are age and ovarian reserve, but other factors such as male pathology and laboratory techniques must be studied deeper.